Proposed Performance Management System for Hanifa Islamic School Using Integrated Performance Management System - Chairuna, Dina; Wibisono, Dermawan (The Indonesian Journal of Business Administration, 2017)
Abstract - Hanifa Islamic School is an organization that specializes in early childhood education. In the world of education, management as a discipline plays a very important role in realizing quality education system and sustained where management is seen as a series of activities or processes that can integrate a variety of sources in order to achieve organizational goals that have been determined. The rapid development of education, especially in the area of South Tangerang characterized by a number of institutions that continue to grow claim Hanifa Islamic School to be able to compete with the newcomer and existing schools. It is therefore necessary to have systems that can help Hanifa Islamic School to simultaneously improve and maintain performance so that it can compete and continue to grow. Using the Integrated Performance Management System (IPMS) of Wibisono, 2012, can be proposed a performance framework that is simple and can reflect the comprehensive performance using a resource perspective, organizational output, perspective, and an internal process perspective that all integrated. As well as conducting benchmark with other school to review the performance system made. These designed IPMS should encourage Hanifa Islamic School to think forward and challenge to improve the performance measurement more effective. The IPMS design will cover several aspects on each perspective. In Resource availability perspective the aspect will be Human Capital, Organization Capital, Technology and Infrastructure Capital. In Internal process perspective will cover Operation aspect and marketing aspect and lastly Organization output perspective will cover Financial and Non Financial Aspects. In this final project the design of performance management system made to be implemented for overall management of Hanifa Islamic School. The final stage that needs to be done is the implementation of performance management systems. The main four foundations in implementation of Performance Management System is the performance measurement, measurement result evaluation, diagnosis for identifying improvement process, and follow-up.Keywords: management, performance management, integrated performance management system, the education industry, Hanifa Islamic School